2023
DOI: 10.1101/2023.02.06.527294
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pupil dilation and microsaccades provide complementary insights into the dynamics of arousal and instantaneous attention during effortful listening

Abstract: Listening in noisy environments requires effort - the active engagement of attention and other cognitive abilities, as well as increased arousal. The ability to separately quantify the contribution of these components is key to understanding the dynamics of effort and how it may change across listening situations and in certain populations. We concurrently measured two types of ocular data in young participants (both sexes) - Pupil dilation (PD) (thought to index arousal aspects of effort) and Microsaccades (M… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 78 publications
1
4
0
Order By: Relevance
“…Eye movements reflect listening challenges differently than the pupil size Recent works suggest that reductions in eye movements may index effort. Eye movements decrease when individuals perform a high-load compared to a low-load memory task (Lipton et al, 1980;Hutton and Tegally, 2005;Kosch et al, 2018;Walter and Bex, 2021) and when speech masking increases (Contadini-Wright et al, 2023;Cui and Herrmann, 2023). We also found that gaze dispersion decreased with decreasing SNR (Figures 2, 4, and 5), and extend this previous work by showing that the sensitivity of eye movements to changes in speech masking does not differ between younger and older adults.…”
Section: Pupil Size Reflects Effortsupporting
confidence: 87%
See 2 more Smart Citations
“…Eye movements reflect listening challenges differently than the pupil size Recent works suggest that reductions in eye movements may index effort. Eye movements decrease when individuals perform a high-load compared to a low-load memory task (Lipton et al, 1980;Hutton and Tegally, 2005;Kosch et al, 2018;Walter and Bex, 2021) and when speech masking increases (Contadini-Wright et al, 2023;Cui and Herrmann, 2023). We also found that gaze dispersion decreased with decreasing SNR (Figures 2, 4, and 5), and extend this previous work by showing that the sensitivity of eye movements to changes in speech masking does not differ between younger and older adults.…”
Section: Pupil Size Reflects Effortsupporting
confidence: 87%
“…Gaze dispersion is a broad measure that captures any eye movements. Analyses of saccades (including microsaccades) require setting a velocity threshold to determine what counts as a saccade (Engbert and Kliegl, 2003;Engbert, 2006;Widmann et al, 2014;Kadem et al, 2020;Contadini-Wright et al, 2023;Cui and Herrmann, 2023), but the threshold can influence whether or not effects of cognition on saccades can be observed (Cui and Herrmann, 2023). Nonetheless, we explored the sensitivity of saccades to changes in SNR and results were very similar to the results for gaze dispersion.…”
Section: Processing Of Pupil-size and Eye-movement Datamentioning
confidence: 84%
See 1 more Smart Citation
“…Some of these neurons show a transient change in their activity when acquisition of reward requires expenditure of physical effort (Bornert and Bouret, 2021). However, the link between effort costs and pupil size appears to go beyond motor control, as a recent paper found that pupil size increases during effortful speech perception (Contadini-Wright et al, 2023). Thus, although in our work increases in pupil size were always associated with increased movement vigor, the results from other studies suggest that economic variables such as cognitive effort in tasks in which there is no concomitant movement also drive an increase in pupil size.…”
Section: Reviewer #1 (Public Review)mentioning
confidence: 99%
“…Gradual changes in sustained MS incidence have been consistently associated with the attentional load experienced by individuals (Pastukhov and Braun, 2010; Benedetto et al, 2011; Siegenthaler et al, 2014; Widmann et al, 2014; Dalmaso et al, 2017; Lange et al, 2017; Yablonski et al, 2017; Abeles et al, 2020; Badde et al, 2020; Contadini-Wright et al, 2023). For instance, MS rate gradually reduces in anticipation, and during the processing of predictable behavioural targets (Abeles et al, 2020; Contadini-Wright et al, 2023).…”
Section: Introductionmentioning
confidence: 99%